2023
DOI: 10.1038/s41467-023-37900-3
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns and edaphic-climatic controls of soil carbon decomposition kinetics predicted from incubation experiments

Abstract: Knowledge about global patterns of the decomposition kinetics of distinct soil organic matter (SOM) pools is crucial to robust estimates of land-atmosphere carbon fluxes under climate change. However, the current Earth system models often adopt globally-consistent reference SOM decomposition rates (kref), ignoring effects from edaphic-climate heterogeneity. Here, we compile a comprehensive set of edaphic-climatic and SOM decomposition data from published incubation experiments and employ machine-learning techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…It can be seen from Section 3.5 that soil pH significantly affected the process of soil C degradation and fixation in the cotton fields. This could be attributed to the fact that soil pH played the most pivotal role in regulating the potential decomposition rate of stable soil organic C pools ( Xiang et al, 2023 ). Soil pH was also the main factor affecting the microbial function of the soil N cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen from Section 3.5 that soil pH significantly affected the process of soil C degradation and fixation in the cotton fields. This could be attributed to the fact that soil pH played the most pivotal role in regulating the potential decomposition rate of stable soil organic C pools ( Xiang et al, 2023 ). Soil pH was also the main factor affecting the microbial function of the soil N cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated a strongly correlation between soil microbial functional genes and taxa abundance with soil environmental factors (Cui et al, 2016;Guo et al, 2023;Xiang et al, 2023). Loganathachetti et al (2022) proposed that soil salinity was an important determinant of bacterial richness and shannon diversity index.…”
Section: Introductionmentioning
confidence: 99%
“…The high content of iron and aluminium in the sludge, which had been added to wastewater in the treatment plant for precipitating phosphorus, and high concentrations of heavy metals during the early decades of the experiments, may also have decreased its accessibility for decomposers (Börjesson et al, 2014). The low soil pH in the sludge treatment and high concentrations of free aluminium and iron may also have affected decomposition (Xiang et al, 2023) as well as soil structure ( Šimanský & Jonczak, 2020). However, the relatively low impact of SOC on PAWC in the treatments with high SOC does not reflect the overall effect of the peat and sludge treatments on water storage because our analysis was limited to the upper 20 cm of the soil profile.…”
Section: Effects Of Soc On Pawcmentioning
confidence: 99%
“…SOM levels (but also bulk density allowing for oxygen transfer and better combustion) can vary locally in Europe, depending on factors like local climate and specific soil and leaf types. These traits, such as pH (Xiang et al, 2023) and leaf types (needles vs. broadleaves) can influence decomposition rates (Masuda et al, 2022;Krishna and Mohan, 2017;Cornelissen et al, 2011), highlighting the potential of using key plant traits as surrogates for SOM assessment. While SOM databases remain somewhat uncertain (Lin et al, 2022) insights from plant traits can be valuable.…”
Section: Future Directions For Soil Combustion Modeling In Europementioning
confidence: 99%